Sētthakit phō̜phīang lō̜līang chumchon (Sūn Chūailư̄a thāng Wichākān Phatthanā Chumchon Khēt thī 10, Krom Kānphatthanā Chumchon, Krasūang Mahātthai, 2007)
Self-sufficiency economy the theory of King Bhumibol Adulyadej and the economic conditions in Thailand.